1975
DOI: 10.1126/science.1145205
|View full text |Cite
|
Sign up to set email alerts
|

Strain Differences During Intraventricular Infusion of Norepinephrine: Possible Role of Receptor Sensitivity

Abstract: Two rat strains previously shown to differ with respect to behavioral activity, regional brain tyrosine hydroxylase activity, and norepinephrine-elicited accumulation of adenosine 3', 5'-monophosphate exhibited differential behavioral responsiveness during the intraventricular infusion of norepinephrine. The results are interpreted in terms of differential catecholamine receptor sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, both rats of the latter strain and animals treated with PNMT inhibitors also show an equal upregulation of the density of brainstem a 1 -adrenoceptors (presumably postsynaptic to the source of EPI) and, in addition, an enhanced motor response to ivt. catecholamine injection (Segal et al, 1975), suggesting that brain a 1 -as well as a 2 -adrenoceptors are innervated by EPI. This agrees with the finding that EPI has the highest efficacy of all tested catecholamines at a 1 -receptors coupled to phosphatidylinositol hydrolysis or potentiation of cAMP responses in rat brain slices (Johnson and Minneman, 1986).…”
Section: Epi As An Endogenous Neurotransmitter At a 1 -Receptorsmentioning
confidence: 98%
“…However, both rats of the latter strain and animals treated with PNMT inhibitors also show an equal upregulation of the density of brainstem a 1 -adrenoceptors (presumably postsynaptic to the source of EPI) and, in addition, an enhanced motor response to ivt. catecholamine injection (Segal et al, 1975), suggesting that brain a 1 -as well as a 2 -adrenoceptors are innervated by EPI. This agrees with the finding that EPI has the highest efficacy of all tested catecholamines at a 1 -receptors coupled to phosphatidylinositol hydrolysis or potentiation of cAMP responses in rat brain slices (Johnson and Minneman, 1986).…”
Section: Epi As An Endogenous Neurotransmitter At a 1 -Receptorsmentioning
confidence: 98%
“…Some studies report large strain differences, which under controlled environmental conditions, could be due to genetic differences. Rat strains have also been found to be differentially sensitive to amphetamines (Camp et al, 1994;Miserendino et al, 2003;Segal et al, 1975), and one study found that the strain distribution patterns for sensitivity to the locomotor stimulant effects of cocaine and d-amphetamine were not identical (George et al, 1991). However, even for two of the most commonly used inbred mouse strains (or sometimes their sublines), C57BL/6 and DBA/2, the strain sensitivity order for amphetamine locomotor response has not been consistent (Anisman et al, 1975;Cabib et al, 2000;Orsini et al, 2004;Phillips et al, 1994;Remington and Anisman, 1976;Wenger, 1989;Zocchi et al, 1998).…”
Section: Inbred Strain Studiesmentioning
confidence: 99%
“…As pioneered by the Segal laboratory and others, animal models of locomotor behavior have been critical tools for understanding the relationships between monoamines and behavior (Geyer and Segal, 1991;Kelly and Iversen, 1976;Lat, 1965;Schiorring, 1979;Segal et al, 1975Segal et al, , 1971Segal and Mandell, 1970;Stinus et al, 1980). Such behavioral models have provided a foundation for much of what we know regarding the neural correlates of behavioral effects of drugs of abuse, in particular psychotomimetics such as stimulants and hallucinogens (Adams and Geyer, 1982;Bankson and Cunningham, 2001;Creese, 1983;Eilam et al, 1989;Fink and Morgenstern, 1985;Geyer, 1990;Lehmann-Masten and Geyer, 1991;Segal, 1975;Segal et al, 1981Segal et al, , 1980Swerdlow and Koob, 1985).…”
Section: Introductionmentioning
confidence: 99%